Remembering and Forgetting: Lizkor VeLishkoach for String Quartet, after Schubert - Biró, Dániel (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractLizkor VeLishkoach (to Remember and to Forget) is a piece that is to be played together with Franz Schubert’s Quartet in G Major D887. Lizkor VeLishkoach (hebrew for “to remember and to forget”) forms its meaning from the roots of the words of its title. The root of “lizkor” is “zekher”, which means both “memory” and “imprint.” Embedded within the verb “lishkoakh” is the word “koakh” meaning “power.” In this paper, I explore aspects of time, memory and place within my quartet, aspects that have become “imprinted” within a personal subjective and larger collective memory. Investigating my own reaction to Schubert’s quartet, I examine how its form and material is re-collected within my own composition. Retracing the re-membering of Schubert’s quartet, I also speculate about my own re-membering and forgetting within the context of this chosen form.